Management of Majelis Taklim in Improving Religious Activities: Case Study of Majelis Taklim Az-Zahra, Maracang Village, Babakancikao District - Ramdani, Fazri; Wulandari, Dyah; Sanusi, Munawar (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2025)
This study is motivated by the importance of management in improving the effectiveness of religious activities in majelis taklim, particularly in responding to the challenges of modernization, lack of innovation, and weak community participation. The purpose of this study is to analyze and describe the implementation of religious activity management applied by Majelis Taklim Az-Zahra. The research focuses on how managerial functions, including planning, organizing, implementing, and supervising, are carried out in the context of increasing community participation in religious activities. This study employs a descriptive qualitative approach using the case study method. Data were collected through in-depth interviews, participatory observation, and documentation. The results of the study indicate that the management of religious activities is carried out systematically and adaptively, with a family-oriented character and an approach based on Islamic values. The use of digital technology and Islamic art further enhances the appeal and effectiveness of the programs implemented.